Hosting and Human Rights: The Summer Olympics in the Twenty-First Century - Ross, MacIntosh; McDougall, Michael (Frontiers in Sports and Active Living, 2022)
Throughout the twenty-first century, Olympic hosts have used the Games to generate a temporary period of exceptional circumstances, using the distractions afforded by the world’s largest multi-sport mega event to justify acts of surveillance, securitization, and displacement. Following the work Antonio Gramsci and his intellectual descendants, we argue that the process by which such intrusions upon civil liberties are normalized, reproduced, and contested are best theorized and understood via the Italian Marxist’s reconceptualization of hegemony. In order to grasp the global implications of the Olympic industry’s infringement of civil rights.In order to grasp the global implications of the Olympic industry’s infringement of civil rights, as well as to identify their partners the world over, this paper is also situated within the field of International Relations (IR), building upon the foundations laid by Neo-Gramscian scholars such as Robert W. Cox (1981, 1987), Stephen Gill (1993), and Owen Worth (2011), to extract aspects of Gramsci’s work from more nationally oriented topics – which guided much of his famous Prison Notebooks – for use on an international scale. Yet, at the same time, we embrace Worth’s (2011) call to experiment with a plurality of Gramscian in IR, using an expansive, cultural approach, rooted in the works of cultural studies pioneer Raymond Williams (1973). In situating sport within the field of IR this article sails in largely uncharted scholarly waters. Writing in 1986, IR scholar Trevor Taylor lamented that the relationship, or lack thereof, between academic work in sport and IR was “a case of mutual neglect” (p. 27). As Alison and Monnington (2005) explain, little progress was made over the next two decades, concluding “the sporting dimension of International Relations still often plays no part in education on the subject” (p. 5). The International Olympic Committee (IOC) and Olympic Games, encompassing a membership of 206 National Olympic Committees (NOCs), seem particularly worthy of IR’s attention.